Brand Identity in Luxury Fashion: Tommy Hilfiger Case Study - Dombrowska, Julia (Tożsamość marki w modzie luksusowej: studium przypadku firmy Tommy Hilfiger, 2025)
A significant aspect of the luxury fashion market is brand identity, which is important to relations with consumers. Despite its importance, brand identity in the luxury fashion industry is under-researched. Most studies focus on broader marketing techniques and financial performance, overlooking the importance of creating a corporate identity. This article defines luxury in historical, psychological, and economic terms. The author also focuses on consumer behaviour and market segmentation, referring to major players such as LVMH and Chanel, and examines market segmentation. She explores consumer loyalty and the role of brand identity in shaping perceptions through symbolism, heritage, and exclusivity. The study covers three topics: consumer understanding of brand identity, its impact on perception of luxury brands, and on customers. The qualitative approach, which included interviews with a sales representative and customers in the fashion industry, revealed that consumers have little understanding of brand identity and are unable to describe it. The results show that a strong brand identity fosters emotional bonds, loyalty, and support, thus influencing customer expectations and satisfaction. The availability of luxury consumer and retail outlets in Poland is very limited, which is why the study included participants from both Poland and the UK.
Quote as: Dombrowska, J. (2024). Brand Identity in Luxury Fashion: Tommy Hilfiger Case Study. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 47-55). Publishing House of Wroclaw University of Economics and Business.
Keywords: brand identity; luxury fashion; consumer perspective; brand identity strategies; tożsamość marki; moda luksusowa; perspektywa konsumenta; strategie identyfikacji marki